PENGARUH BOKASHI KOTORAN SAPI DAN GANDASIL B TERHADAP PERTUMBUHAN SERTA PRODUKSI MENTIMUN (Cucumis sativus L.) - Afdhal, Muhammad Shifhi; MuFauzan, MuFauzan; Wirawan, Purnama (Jurnal Pertanian Khairun, 2025)
This study aimed to evaluate the effects of combining cow manure bokashi and Gandasil B foliar fertilizer on the growth and yield of cucumber (Cucumis sativus L.) variety Hercules F1. The experiment was conducted using a factorial Completely Randomized Design (CRD) with two factors: bokashi dosage (0, 10, 15, and 20 tons/ha) and Gandasil B concentration (0, 5, 7, and 9 g/L), each repeated three times, resulting in 48 experimental units. Observed parameters included plant height, leaf number, number of fruits per plant, fresh fruit weight, and fruit length. The results showed that the combination of 15 tons/ha bokashi and 7 g/L Gandasil B (A3B3) significantly produced the best results across all parameters. This treatment improved nutrient availability, enhanced soil structure, and supported plant physiological efficiency. Therefore, the integrated application of cow manure bokashi and Gandasil B is an effective and sustainable fertilization strategy to increase cucumber productivity.